A Power Stronger than Itself: The AACM and American Experimental Music - Lewis, George E. (Chicago University of Chicago Press, 2008)
Founded in 1965 and still active today, the Association for the Advancement of Creative Musicians (AACM) is an American institution with an international reputation. George E. Lewis, who joined the collective as a teenager in 1971, establishes the full importance and vitality of the AACM with this communal history, written with a symphonic sweep that draws on a cross-generational chorus of voices and a rich collection of rare images.Moving from Chicago to New York to Paris, and from founding member Steve McCalls kitchen table to Carnegie Hall, A Power Stronger Than Itself uncovers a vibrant, multicultural universe and brings to light a major piece of the history of avant-garde music and art.
Keywords: Music history; Avant-garde; USA